(untitled) (Medical Forum Monthly, 2026)
Objective: To compare the efficacy and safety of dexmedetomidine versus quetiapine for the treatment of delirium among critically ill patients admitted to the Intensive Care Unit (ICU). Study Design: Randomized Controlled trial studyPlace and Duration of Study: This study was conducted at the Combined Military Hospital, Lahore from October 2025 to December 2025. Methods: A randomized controlled trial was conducted on 70 ICU patients diagnosed with delirium, who were allocated to receive either dexmedetomidine or quetiapine. Primary outcomes included time to delirium resolution, ICU length of stay, number of delirium days, and mortality. Secondary outcomes assessed adverse events and cost effectiveness. Results: Dexmedetomidine demonstrated superior clinical performance, with faster delirium resolution, reduced ICU and hospital stay, and lower mortality compared to quetiapine. It also showed a more favorable safety profile with fewer adverse events, particularly lower rates of hypotension and excessive sedation. Conclusion: Dexmedetomidine appears to be a more effective and safer option than quetiapine for managing delirium in ICU patients. Further multi-center trials are recommended to validate these findings and assess long- term outcomes.